Neuro-exoscopic clipping of ruptured basilar apex aneurysm: a step-by-step video - KP, Priyadharshan; M, Naveen Kumar; Narayanan, Swarnarekha; M, Kodeeswaran (Journal of Neurosurgery Academy, 2025)
This article presents a step-by-step video demonstrating neuro-exoscopic clipping of a ruptured basilar apex aneurysm in a 68-year-old female. The neuro-exoscope provided enhanced visualization and improved surgeon ergonomics, facilitating precise clip placement. Despite intraoperative rupture, immediate control was achieved. The case underscores the advantages of the exoscope in managing complex posterior circulation aneurysms, offering a viable alternative to endovascular treatment. Key surgical nuances and postoperative considerations are discussed to aid neurosurgeons in refining their approach.